Brucella abortus-infected platelets adctivate the endothelium and promote the migration of monocytes towards the site of infection - Trotta, Aldana (2018)
Brucellosis is an infectious disease elicited by bacteria of the genusBrucella. Platelets have recently got involved in the modulationof innate and adaptive immune responses. We have previously reportedthat platelets act as carriers of bacteria, promoting the invasionof monocytes. Thus, the aim of this study was to further investigatethe role of platelets in the immune response against Brucella.First, we wondered whether the presence of platelets modulates thetime course of B. abortus infection. For this, THP-1 cells (humanmonocytic cell line) were infected with B. abortus in presence orabsence of platelets. Then, extracellular bacteria were killed andcells were incubated for different times. Our results demonstratethat the presence of platelets significantly increased the percentageof B. abortus-infected THP-1 cells at early time-points (p<0.001).Nevertheless, the presence of platelets subsequently improvedthe contention of the infection. Taking into consideration that B.abortus localization within different tissues requires its extravasationacross the endothelium, our next aim was to study the role ofplatelets in the modulation of monocytes extravasation in the contextof B. abortus-mediated infection. We first studied the ability ofplatelets to recruit monocytes. Our results showed that supernatantscollected from infected platelets promote the transmigrationof monocytes (p<0.01). Moreover, the pre-treatment of monocyteswith this supernatant enhance the responsiveness of monocytestowards other chemoattractant stimuli (p<0.01). Finally, we studiedthe ability of platelets to activate the endothelium. For this, HMECcells (human endothelial cell line) were stimulated with supernatantscollected from B. abortus-infected platelets. This supernatant stimulatedthe expression of ICAM-1 (CD54) (p<0.01). At the same time,it enhanced the secretion of both IL-8 and MCP-1 (p<0.01). Theseresults showed that infected platelets are able to activate the endotheliumand promote the migration of monocytes towards the site ofthe infection.